2020
DOI: 10.1080/15476286.2019.1700033
|View full text |Cite
|
Sign up to set email alerts
|

Study on the efficiency of dsRNAs with increasing length in RNA-based silencing of the Fusarium CYP51 genes

Abstract: Previously, we have demonstrated that transgenic Arabidopsis and barley plants, expressing a 791 nucleotide (nt) dsRNA (CYP3RNA) that targets all three CYP51 genes (FgCYP51A, FgCYP51B, FgCYP51C) in Fusarium graminearum (Fg), inhibited fungal infection via a process designated as host-induced gene silencing (HIGS). More recently, we have shown that spray applications of CYP3RNA also protect barley from fungal infection via a process termed spray-induced gene silencing (SIGS). Thus, RNAi technology may have the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 58 publications
6
46
0
Order By: Relevance
“…Notably, we demonstrated previously that Fg can take up long, unprocessed dsRNA that is processed by its own RNAi [6,7]. This finding, which may explain why we observed greater silencing efficacy in the fungal target genes [8], indicates that fungi, like insects, seem to respond more efficiently to dsRNA than to siRNA. Feeding on dead plant tissue, necrotrophic fungi may take up topically applied dsRNA or dsRNA delivered to the xylem [6].…”
Section: Introductionsupporting
confidence: 59%
“…Notably, we demonstrated previously that Fg can take up long, unprocessed dsRNA that is processed by its own RNAi [6,7]. This finding, which may explain why we observed greater silencing efficacy in the fungal target genes [8], indicates that fungi, like insects, seem to respond more efficiently to dsRNA than to siRNA. Feeding on dead plant tissue, necrotrophic fungi may take up topically applied dsRNA or dsRNA delivered to the xylem [6].…”
Section: Introductionsupporting
confidence: 59%
“…Moreover, using transgenic Arabidopsis expressing the dsRNA CYP3RNA we demonstrate that EVs carry transgene-derived siRNA cargo ( Figure 2). Previous work showed that the 791 nt long CYP3RNA, when expressed in Arabidopsis or barley, inhibits the infection Fg by targeting the transcripts of its three FgCYP51 genes via RNAi [12,47,71]. Together these findings support the view that HIGS includes processing of dsRNA in the plant, incorporation of the produced siRNA into intracellular vesicles, secretion of the vesicles into the apoplastic space, and a potential uptake of the vesicles or their cargo into the interacting fungus ( Figure 6).…”
Section: Discussionsupporting
confidence: 74%
“…1h and 1i). This finding—along with previously discovered differences in efficiencies between dsRNA originating from endogenous expression (HIGS) and dsRNA originating from exogenous spray 10 —underlines mechanistic differences between HIGS and SIGS regarding dsRNA uptake, processing, and transfer. In sum, our current knowledge supports a model of HIGS that involves both plant Dicer-mediated processing of transgene-derived dsRNA into siRNAs and ESCRT-III components mediating RNA transfer—possibly via EVs.…”
Section: Resultssupporting
confidence: 66%